At-Tarbiyatul Khuluqiyyah: Dirasat al-Muqaranah baina Afkari al-Ghazali wa Tamathul Lichona. - Casrameko _ (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2015)
Character education has been a topical theme amongst educatiors. A deep and thorough investigation of concepts elaborating the theme proves to be not an easy task. From Islamic persepective, Al-Ghazali was famous for his thingking of soul purification. Prerequisites, procedures, crucial elements of such purification are considered to offer an abundance of approaches in character building. From the West, Thomas Lickona offers fundamental construction of character building. Fundamental ideas of the two figures will be studied and analysed so as to come to a thick description of differences and similarities between them.